Taib: integrity crucial for success: Employees advised to protect their organisation's interest before their own - Yeo, Calvin (The Star, 2013)
KUCHING: Chief Minister Tan Sri Abdul Taib Mahmud wants employees to embrace three basic values for their organisations to proper.